Indicators of the Quality of Work in Residential Treatment Centres - Krajnčan, Mitja (Revija za elementarno izobraževanje, 2021)
In the last year, residential treatment centres in Slovenia have made a significant shift from traditional approaches to programs for young people which are adapted to their needs within the entire continuum of help: from preventive work to early detection, a range of support programs, various programs in out-ofhome care, and intensive treatment, up to the most difficult cases. It is therefore important that the work be properly reflected through quality settings. These concern all aspects of an institution's operation. Using a comparative method of comparing sources and analytical synthesis, we have shown all the important areas of operation of such a system. Orientation towards the areas of work quality represents a modern and current discourse, while simultaneously providing starting points for development.
Keywords: residential teratment centre; behavioural and emotional problem/disorders; professionla centre; quality of work; forms of educational help